2016
DOI: 10.1016/j.dyepig.2016.03.044
|View full text |Cite
|
Sign up to set email alerts
|

pH triggered smart organogel from DCDHF-Hydrazone molecular switch

Abstract: The design, synthesis and photophysical properties of a Low Molecular Weight pH-responsive Gelator (LMWG) based on alkoxy group functionalized DCDHF-Hydrazones (DCDHF-H) are described. A straightforward synthesis of DCDHF-Hydrazone (DCDHF-H) chromophores was achieved via simple azo-coupling starting from 2-(dicyanomethylene)-2,5-dihydro-4,5,5trimethylfuran-3-carbonitrile and alkoxy bearing aryl diazonium chloride derivatives. The DCDHF-H efficiently gelate selected organic solvents and reversibly respond to pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…The gelation studies of the minimum gel concentration values are displayed in Table . The minimum gelation concentration values demonstrate solvent dependent performance and occur in the range of 2.38 and 9.63 m m which is comparable to a variety of reported organogelators containing long alkoxy side chains …”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The gelation studies of the minimum gel concentration values are displayed in Table . The minimum gelation concentration values demonstrate solvent dependent performance and occur in the range of 2.38 and 9.63 m m which is comparable to a variety of reported organogelators containing long alkoxy side chains …”
Section: Resultssupporting
confidence: 80%
“…Recently, low molecular‐weight organogelators (LMOGs) have attracted considerable interest due to the large diversity of gelators giving rise to thermally reversible organogels in different solvents . The distinct capability of small organogelator to solidify and hold organic liquids via weak non‐covalent interactions such as π‐π stacking, push‐pull systems, hydrogen bonding, and van der Waals interactions, has received significant attention . It is significant to control such intermolecular forces in a way that the gelator molecules can self‐assemble into fibrous higher order assemblies but without switching into dense crystals .…”
Section: Introductionmentioning
confidence: 99%
“…The synthetic approach for the TCFH chromophores 3a‐d employed in this study is shown in Figure . The azo‐coupling reaction occurs in alkaline medium between the diazonium salt and tricyanofuran heterocycle bearing active methyl group to afford the corresponding unstable azo‐product that transforms directly to the more stable hydrazone‐form . The hydrazone N−H functional group was confirmed by 1 H NMR at 12.27‐12.66 ppm; and by FT‐IR at 3241–3392 cm −1 .…”
Section: Resultsmentioning
confidence: 98%
“…The choice of aromatic amines to produce the corresponding diazonium salts were selected to contain weak electron donating and withdrawing substituents as our earlier publications for TCF‐hydrazone dyes indicated high effects with highly electron donating and withdrawing substituents . The UV‐Vis absorption and fluorescence spectra of the TCF‐based aryl‐hydrazones 3a‐d in a variety of solvents with different polarities are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation